Eltrombopag for the treatment of thrombocytopenia in patients with malignant and non-malignant hematologic disorders. (December 2013) - Pathak, Swati; Roth, Michael; Verma, Amit; Steidl, Ulrich
Abstract : Introduction: Eltrombopag (EP) is an orally bioavailable, non-peptide, thrombopoietin receptor (TPO-R) agonist developed to stimulate platelet production. EP is a small hydrazone molecule which interacts with the transmembrane domain of TPO-R and promotes megakaryopoiesis, and a subsequent increase in platelet number. To date, multiple large clinical trials have demonstrated the ability of EP to reduce the burden of thrombocytopenia and its associated side effects in patients with chronic immune thrombocytopenia purpura and patients with hepatitis-C related thrombocytopenia. Given these promising results and the morbidity associated with thrombocytopenia in cancer patients, there is significant interest in investigating the role of EP for thrombocytopenia secondary to myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). Areas covered: In this review, the authors address the potential utility of EP for patients with AML and MDS with thrombocytopenia. The review provides an overview of the rationale for the development of EP in AML and MDS, and the mechanism(s) of action of EP. The authors focus on preclinical data describing the effectiveness of EP as both a platelet-stimulating, and an anti-leukemia agent and describe the use of EP in clinical trials. Expert opinion: EP has the potential to be an effective supportive care agent, improving platelet counts and decreasing thrombocytopenia-related morbidity, in patients with AML and MDS. Large, randomized clinical trials are needed to assess the efficacy of EP in reducing the duration and severity of thrombocytopenia, as well assess the clinical utility of EP as an anti-leukemia agent.